THE EFFECT OF PRE-QUESTIONING TECHNIQUE ON READING COMPREHENSION AT VIII GRADE STUDENTS OF SMPN 16 MANDAU - Eka Melati (Universitas Mahaputra Muhammad Yamin, 2019)
Reading becomes more crucial in education field. A student needs to be exercised and trained in order to have a good reading skill. It is also indispensable for the student because one criteria of a successful student in her study depends on her ability to read. But most of the students faced difficulty in applying the reading skill. Pre-questioning technique is suggested in this research. The purpose of this research was to know the effect of pre-questioning technique on student’s reading comprehension. This study was a quasi-experimental research. Population of this study was VIII grade students of SMPN 16 Mandau for 2017/2018 academic year. The sample was VIII-3 class as experimental group and VIII-7 class for control group which selected by using cluster random sampling technique. Test of reading comprehension was the instrument. The data were analyzed by t-test. From this study, it was computed that tobserved (3.38) was higher than ttable (1.73). If tobserved was higher than ttable it meant alternative hypothesis (Ha) accepted. It can be concluded that pre-questioning technique produced better result on reading comprehension. Pre-questioning technique could be implemented as one of the technique in teaching reading at SMPN 16 Mandau.